Hubungan Motivasi Keluarga Terhadap Tingkat Kemandirian Lansia Di Uptd Puskesmas Kecamatan Pontianak Barat Tahun 2014 - Jiu, Cau Kim; Rahayu, Indah Dwi; Aliana, Ande (Jurnal Keperawatan dan Kesehatan, 2014)
Background: Problems population and health may occur due to aging population. One of the problems arising from the increase in the elderly population is the increase in the elderly dependency ratio. Maintaining independence in older adults who are already self-sufficient is very important that the elderly can take care of herself in meeting basic human needs such as in performing daily activities. Objectives: The purpose of this study was to determine the correlation of family motivation to the degree indepence of elderly. This study used quantitative research design used is analytic approach Cross Sectional with a sample of 341 elderly people in UPTD Puskesmas Kecamatan Pontianak Barat. Sampling in this study using probability sampling the technique simple random sampling. Methods of data collection using questionnaire. Data analysis is performed using univariate and bivariate test spearman rank. Methods: The results of the study, based on analysis result obtained significant value (p = 0.530> p = 0.05) which indicates that there was not significant correlation between the degree of independence of family motivation elderly and Spearmen rank correlation value of r = 0.34 indicates that the direction of a positive correlation with the strength of the correlation is weak, while the result of age values obtained significancy (p = 0.001 <p = 0.05) which indicates that was significant correlation between the degree of independence of elderly age. Spearman correlation value of r = 0.173 shows that the direction of a positive correlation with the strength of the correlation is very weak. Results: for the significant (p value) indicates that there is a signigicant correlation between age and the level of independence of the elderly and (spearmen rank) correlation value indicate that the direction of the positive correlation with the strength of the correlation is very week. Conclusion: There is correlation between age and the level of independence of the elderly